Tailored Bioactive Compost from Agri-Waste Improves the Growth and Yield of Chili Pepper and Tomato - Imran, Asma; Sardar, Fozia; Khaliq, Zabish; Nawaz, Muhammad Shoib; Shehzad, Atif; Ahmad, Muhammad; Yasmin, Sumera; Hakim, Sughra; Mirza, Babur S.; Mubeen, Fathia; Mirza, Muhammad Sajjad (Frontiers in Bioengineering and Biotechnology, 2022)
The extensive use of chemical fertilizers has posed a serious impact on food safety and environmental sustainability. The use of organic or biofertilizers can lower down the chemical residues in the food and environment. The agriculture crop residues (waste) being a rich source of nutrients, can stimulate the growth of the other crops after composting, hence can be used to promote organic agriculture. This study demonstrates a feasible strategy to convert the plant residues (wheat and rice) into composted organic fertilizer after enrichment with plant-beneficial bacteria instead of open-field burning. The bioactive compost was then tested in series of in vitro and in vivo experiments for validating its role in growing organic vegetables. The compost was enriched with a blend of micronutrients zinc, magnesium and iron and multi-trait bacterial consortium-AAP (Azospirilum, Arthobacter, and Pseudomonas spp.). The bacterial consortium AAP showed survival up to 180 days post-inoculation while maintaining their PGP traits. FESEM analysis and fluorescence in situ hybridization (FISH) of bioactive compost further elaborated the morphology and confirmed the PGPR-survival and distribution. Plant-inoculation of this bioactive compost showed significant improvement in chilies and tomato growth and yield without any additional chemical fertilizer. An increase of ≈35% in chlorophyll contents, ≈25% in biomass, and ≈75% in yield was observed in chilies and tomatoes. The increase in N was 18.7 and 25% while in P contents were 18.5 and 19% in chilies and tomatoes, respectively. The application of bioactive compost significantly stimulated the bacterial population as well as the phosphatase and dehydrogenase activities of soil. These results suggest that bioactive compost can serve as a source of bio-organic fertilizer to get maximum benefits regarding vegetable yield, soil quality, and fertilizer saving with the anticipated application for other food crops. It is a possible win-win situation for environmental sustainability and food security.